A tapestry of light - Duffy, Kimberly (Bethany House Publishers, a division of Baker Publishing Group, 2021)
"When a stranger appears in India with news that Ottilie Russell's brother must travel to England to take his place as a nobleman, she is shattered by the secrets that come to light. But betrayal and loss lurk in England too, and soon Ottilie must fight to ensure her brother doesn't forget who he is, as well as stitch a place for herself in this foreign land"--